Diffrazioni (Due) la psicoanalisi fra Kultur e civilizzazione - Felice Ciro Papparo (Fuori Collana, 2018)
Diffractions. 1994: Philosophy put to test by Psychoanalysis, namely a changing over the method, better to say a style, of the philosophical discourse which "takes care" of other discourses, coming to aid or to annexe them, just because felt/perceived as deficient from the epistemological point of view, as they are no more than empirical knowledges, and thus in need of a "second foundation".Beyond this canon, (it is) the experience of the proof of diffraction, with and within the thought itself, which means a mutual "de-construction and re-construction" of knowledges which assay themselves beyond any foolish and pretentious sovereignism. Diffractions. 2018: Psychoanalysis between Kultur and Civilisation, namely the whole of the cultural products; the social patterns; the political and institutional options; the whole of the values and ideologies that shapes the Kultur itself, diffracted by the psychoanalytical stream, beyond any childish "gentry" of Kultur on Civilisation.